CLINICAL AND PARACLINICAL CHARACTERISTICS OF PATIENTS UNDERGOING LAPAROSCOPIC TRANSABDOMINAL PREPERITONEAL (TAPP) INGUINAL HERNIA REPAIR USING SELF-GRIPPING MESH (Vietnam Journal of Community Medicine, 2026)
ABSTRACTObjective: To evaluate the clinical and paraclinical characteristics of patients with inguinal hernia undergoing laparoscopic transabdominal preperitoneal (TAPP) repair using self-gripping mesh.Subjects and Methods: A descriptive case series combining retrospective and prospective data on 45 patients who underwent TAPP repair for inguinal hernia using self-gripping mesh at Hai Phong University of Medicine and Pharmacy Hospital from January 2025 to December 2025.Results: The mean age was 59.5 ± 12.3 years (range: 23–79), and all patients were male. The mean BMI was 22.4 ± 2.4 kg/m². No patient had an ASA score > III. Common causes of increased intra-abdominal pressure were benign prostatic hyperplasia and constipation (21 patients). There was a significant discrepancy between preoperative and intraoperative diagnosis of bilateral inguinal hernia. On ultrasonography, 16.9% of cases required the Valsalva maneuver to detect hernia contents.Conclusion: Thorough evaluation and analysis of clinical and paraclinical characteristics in each patient are essential for selecting the appropriate treatment approach.
Keywords: Valsalva maneuver, TAPP, self-gripping mesh.